Development of badminton-specific footwork training from traditional physical exercise to novel intervention approaches - Yu, L.; Mohamad, N. I. (Physical Activity and Health, 2022)
Background: Badminton has been one of the most popularised sports and physical activities around the globe with documented healthy benefits. Training of badminton footwork could enable rapid movement velocity thus improving the athletic performance. This study was aimed to review the development of badminton footwork training and summarise the different exercise training approaches and resistance training.